RT-Symmetric Laplace Operators on Star Graphs: Real Spectrum and Self-Adjointness - Maria Astudillo; Pavel Kurasov; Muhammad Usman (Advances in Mathematical Physics)
How ideas of PT-symmetric quantum mechanics can be applied to quantum graphs is analyzed, in particular to the star graph. The class of rotationally symmetric vertex conditions is analyzed. It is shown that all such conditions can effectively be described by circulant matrices: real in the case of odd number of edges and complex having particular block structure in the even case. Spectral properties of the corresponding operators are discussed.